Lanskap Pembelajaran Bahasa Jawa Masa Pandemi Covid-19 (Jurusan Bahasa dan Sastra Jawa Universitas Negeri Semarang, 2022)
Learning Javanese during the Covid-19 pandemic experienced several challenges. On the one hand, it is hoped that this lesson will remain strong as an entry point for the inheritance of noble character through language preservation. While on the other hand, learning Javanese, like a common phenomenon that is also faced by other subjects in schools in Indonesia, is experiencing difficulties due to online learning. This study reveals the phenomena, obstacles, and opportunities of learning Javanese, although in some cases it can also be generalized to other subjects. The design of this study was qualitative, using questionnaires and interviews with parents. This research shows that with the various difficulties faced in learning during the pandemic, face-to-face meetings and conventional learning such as the period before the Covid-19 pandemic were considered irreplaceable. However, our elaboration study shows something else. Learning that is more flexible and involves information technology should be paid more attention to equip students to develop more.